Cross-protective effect of acid adaptation on ethanol tolerance in Salmonella Enteritidis - Shoukui He; Beining Ye; Zengfeng Zhang; Yan Cui; Siyun Wang; Xianming Shi (Food Science and Human Wellness)
Cross protection can undermine the effectiveness of control measures on foodborne pathogens, and therefore brings major implications for food safety. In this work, the capacity of Salmonella Enteritidis to mount ethanol tolerance following acid adaptation was characterized by analysis of cell viability and cell membrane property. It was observed that preadaptation to pH 4.5 significantly (P < 0.05) increased the tolerance of log-phase cells to ethanol; in contrast, stationary-phase cells displayed reduced ethanol tolerance after acid adaptation. However, acid adaptation did not cause cell leakage and morphological change in both log-phase and stationary-phase S. Enteritidis. Fatty acid analysis further revealed that the amount of C14:0, C17:0 cyclo and C19:0 cyclo fatty acids was increased, while that of C16:1ω7c and C18:1ω7c fatty acids was decreased, respectively, in response to acid adaptation, regardless of bacterial growth phase. Notably, acid adaptation significantly (P < 0.05) increased the proportion of C16:0 fatty acid in log-phase cells, but this effect did not occur in stationary-phase cells. Moreover, exogenous addition of C16:0 fatty acid to stationary-phase acid-adapted cultures was able to enhance bacterial ethanol tolerance. Taken together, C16:0 fatty acid is involved in the growth-phase-dependent protective effect of acid adaptation on ethanol tolerance in S. Enteritidis.